2019
DOI: 10.1016/j.gore.2019.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Patients with endometrial cancer continue to lack understanding of their risks for cancer

Abstract: It is unclear if endometrial cancer (EC) patients are aware of their modifiable risk factors. We administered a 33-item questionnaire to EC patients at a university-based cancer center to assess their understanding of how comorbidities and lifestyle/sexual behaviors impact their cancer risk. We also inquired about their access to a primary care physician (PCP). Pearson's χ 2 test or Fisher's exact test were used to assess differences in understanding based on a dichotomized Charlson como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…These data are important for two reasons. First, knowing that cancer initiation and cancer progression is multifactorial, better diagnostic tools such as exosomes are needed [37,38]. Secondly, knowing that cancer progression can be further exasperated by other external stimuli (i.e., nicotine and alcohol) further reiterates the need for better diagnostic tools [35].…”
Section: Introductionmentioning
confidence: 99%
“…These data are important for two reasons. First, knowing that cancer initiation and cancer progression is multifactorial, better diagnostic tools such as exosomes are needed [37,38]. Secondly, knowing that cancer progression can be further exasperated by other external stimuli (i.e., nicotine and alcohol) further reiterates the need for better diagnostic tools [35].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous research reporting that gynecologic cancer patient preferences (38% of whom were EC patients) who understood the importance of weight loss and obesity-related health risks were more likely to believe that weight management counseling would be effective. 38 As a majority of women in the US are not aware of the association between obesity and EC, [39][40][41] these results suggest that increasing obesity-related risk perceptions may increase positive beliefs toward (and ultimate uptake of) lifestyle modification and weight loss programs.…”
Section: Discussionmentioning
confidence: 98%
“…34 Similarly, studies assessing technology-based education platforms have shown that women are amenable to lifestyle modifications. 35 Nontraditional weight loss strategies, as well as pharmacologic and surgical therapies, also have shown benefit in patients in which traditional lifestyle modifications are not sufficient. 36,37 Where physicians can make the most difference is in educating and empowering endometrial cancer survivors to serve as advocates to their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing these knowledge gaps for patients through counseling, combined with technology-based interventions that use smartphone applications and telemedicine, has shown positive results 34 . Similarly, studies assessing technology-based education platforms have shown that women are amenable to lifestyle modifications 35 . Nontraditional weight loss strategies, as well as pharmacologic and surgical therapies, also have shown benefit in patients in which traditional lifestyle modifications are not sufficient 36,37 .…”
Section: Discussionmentioning
confidence: 99%